Ethics of aristotle - Aristotle (Middlesex, 1976)
There were several reasons why J. A. K. Thomson's translation of the Ethics called for a revision. It was written more than twenty years ago, with the object of providing an English version, not of the Greek text, which in many parts of the work is hardly more than a minimal expansion of lecture notes. but of the lectures which Aristotle may be supposed to have actually delivered. The result, although eminently readable, was not achieved without some licence: were omitted; others that seemed loosely parenthetical were represented as footnotes; and such comments or elucidations of Aristotle's meaning as seemed desirable were conveyed by means of expansion or paraphrase.
Keywords: Ethics